Biomimetic and antimicrobial surfaces for orthopedic implants - Wigmosta, Tara, author; Kipper, Matt, advisor; Popat, Ketul, advisor; Giess, Brian, committee member; De Long, Susan, committee member; Schenkel, Alan, committee member (Colorado State University. Libraries, 2021)
The number of total knee and hip replacement surgeries is expected to continue to rise in the United States. As such, the number of revision surgeries is also expected to rise. The two most common causes of failure for these implants is aseptic loosening, caused by incomplete osseointegration, and infection. Therefore, preventing infection while increasing the osteogenic properties of the surfaces used in orthopedic implants could reduce the number of revision surgeries. It is the goal of this work to create nanostructured surfaces that both increase mineralization and antimicrobial properties of titanium surfaces commonly used in orthopedic implants. To accomplish this, chitosan/heparin polyelectrolyte multilayers (PEMs), with the addition of either bone morphogenetic protein 2 (BMP-2) or gentamicin, were adsorbed onto titania nanotubes. BMP-2 has been used in clinical applications to increase osseointegration in spinal fusions, and gentamicin is effective against the most common pathogens found in infected orthopedic implants. Both heparin and chitosan are biocompatible and have antimicrobial properties. BMP-2 has a binding site for heparin that increases BMP-2's half-life in vitro. The first chapter summarizes the motivation and previous strategies used to increase osseointegration and antimicrobial properties of nanostructured biomimetic orthopedic implant surfaces. The first chapter concludes with a shift in hypothesis testing, outlining three different hypotheses: 1) surface modification(s) increase cytocompatibility and the osteogenic properties of mammalian bone cells; 2) surface modification(s) reduce bacterial adhesion, proliferation, and infection rate, without decreasing cytocompatibility; and 3) surface modification(s) provide a favorable environment in which mammalian cells can beat bacterial cells and colonize the surface first, thus increasing the osteogenic and antimicrobial properties of the surface. The testing of these hypotheses are explored in chapters 2 through 4. The second chapter explores hypothesis 1) by testing if BMP-2 released from chitosan/heparin PEM coated titania nanotubes surfaces induce an osteogenic response from rat bone marrow cells. Chapter 3 explores hypothesis 2) by testing if iota-carrageenan/chitosan and pectin/chitosan PEMs have antimicrobial properties against Pseudomonas aeruginosa (P. aeruginosa) and Staphylococcus aureus (S. aureus), and support rat bone marrow cell adhesion and proliferation. The last chapter explores hypothesis 3) by testing if gentamicin released from titania nanotubes coated with chitosan/heparin PEMs influences the "race to the surface" in favor of mammalian cells.